Confidências: os ensaios críticos de Kate Chopin - Rossi, Aparecido Donizete [UNESP] (My University, 2012)
Between 1894 and 1899 Kate Chopin (1850 – 1904), one of the main exponents of American Realism and Feminism, published seven critical essays in newspapers and journals. To this number, it might be added the sketch ―Confidences‖ and the two first entrances of Impressions, her second diary, totalizing nine texts. These texts unveil a refined critical spirit, an outspoken and edge-cutting style in writing, sometimes sarcastically merciless, and an eager reader, all of them aspects that would be put into practice by the Feminist criticism expressed in the author‘s novels and short stories. To introduce and briefly discuss these essays are the main purposes of this paper.

Entre os anos de 1894 e 1899, Kate Chopin (1850 – 1904), um dos principais nomes do realismo e do Feminismo estadunidenses, publicou sete breves ensaios críticos em jornais e periódicos, aos quais se pode acrescentar um rascunho intitulado ―Confidences‖ e as duas primeiras entradas de Impressions, seu segundo diário, em um total de nove textos. Esses escritos revelam um refinado espírito crítico, um estilo de escrita franco e cortante, às vezes sarcasticamente impiedoso, e uma leitora contumaz, aspectos que seriam colocados em prática por meio da crítica feminista expressa nos contos e romances da autora. Apresentar e discutir brevemente tais ensaios são os objetivos deste estudo.
Confidences: Kate Chopin's critical essays
Keywords: Kate Chopin; Literary criticism; Cultural criticism; Feminism; Kate Chopin; Crítica literária; Crítica cultural; Feminismo